Inventory of butterfly species (Lepidoptera: Papilionoidea) in several habitat types in University of Bangka Belitung - Elfrida Natalia Manurung; Budi Afriyansyah; Hari Sutrisno (Universitas Nusa Bangsa, 2021)
Butterflies (Papilionoidea) are Lepidoptera which have various ecological roles in maintaining the balance of the ecosystem and can be found in various types of habitats ranging from forest to urban areas. This research was conducted from March to June 2020 in four types of habitat, namely, rubber gardens, secondary forest, agroecosystem hatchery, and swamp forest using the Pollard transect method and the sweeping net technique for five days in each habitat type. The relationships between environmental factors and the number of species and individuals were analyzed with the Pearson correlation test. The number of individual butterflies obtained was 913 butterflies of 27 species from five families (Nymphalidae, Pieridae, Lycaenidae, Hesperidae, and Riodinidae). The highest diversity was found in rubber gardens (19 species) followed by secondary forest (17 species), swamp forest (12 species) and agroecosystem hatchery (10 species). The highest species diversity index was found in swamp forests, while the lowest was in the agroecosystem hatchery habitat. The types of butterflies found in all habitats are Eurema sari, Mycalesis horsfieldi and M. mineus. The most abundant butterfly family is Nymphalidae. The Pearson correlation test analysis results showed a relationship between environmental factors and the number of species and individuals found.Keywords: Diversity, butterflies, Papilionoidea, habitat ABSTRAKInventarisasi jenis kupu-kupu (Lepidoptera: Papilionoidea) di beberapa tipe habitat di Universitas Bangka Belitung Kupu-kupu (Papilionoidea) merupakan Lepidoptera yang memiliki berbagai peran ekologis dalam menjaga keseimbangan ekosistem serta dapat ditemukan di berbagai macam tipe habitat mulai dari kawasan hutan hingga perkotaan. Penelitian ini dilakukan pada bulan Maret sampai Juni 2020 di empat tipe habitat yaitu, kebun karet, hutan sekunder, hatchery agroekosistem, dan hutan rawa dengan menggunakan metode transek Pollard dan teknik sweeping net selama lima hari di masing-masing tipe habitat. Hubungan faktor lingkungan dengan jumlah spesies dan jumlah individu dianalisis dengan uji korelasi Pearson. Jumlah individu kupu-kupu yang diperoleh sebanyak 913 ekor yang terdiri dari 27 spesies yang berasal dari lima famili (Nymphalidae, Pieridae, Lycaenidae, Hesperidae, dan Riodinidae). Keanekargaman tertinggi didapatkan di habitat kebun karet (19 spesies) selanjutnya diikuti hutan sekunder (17 spesies), hutan rawa (12 spesies) dan hatchery agroekosistem (10 spesies). Indeks keanekaragaman jenis paling tinggi ditemukan di hutan rawa, sedangkan yang paling rendah pada habitat hatchery agroekosistem. Jenis kupu-kupu yang ditemukan di seluruh habitat yaitu Eurema sari, Mycalesis horsfieldi dan M. mineus. Famili kupu-kupu yang paling melimpah Nymphalidae. Hasil analisis uji kolerasi pearson, menunjukkan adanya hubungan antara faktor lingkungan dengan jumlah spesies dan individu yang ditemukan.Kata kunci: keanekaragaman, kupu-kupu, Papilionoidea, habitat